2021
DOI: 10.1136/bmjopen-2020-046935
|View full text |Cite
|
Sign up to set email alerts
|

Detection of intracranial hypertension in children using optical coherence tomography: a systematic review

Abstract: ObjectivesTo evaluate the diagnostic capability of optical coherence tomography (OCT) in children aged under 18 years old with intracranial hypertension (IH).DesignSystematic review.MethodsWe conducted a systematic review using the following platforms to search the keywords ‘optical coherence tomography’ and ‘intracranial hypertension’ from inception to 2 April 2020: Cochrane Central Register of Controlled Trials, EMBASE, MEDLINE, PubMed and Web of Science, without language restrictions. Our search returned 27… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…In our study, as in literature, RNFL thickness in patients with IIH was significantly higher in each quadrants tham among controls. 16,17 Studies on RNFL thickness in patients with ODD, however, have shown varying results. [18][19][20][21] Allegrini et al emphasized that ODD patients had a thinning of the RNFL and thought that this was due to the compression of the drusen material causing axonal damage.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, as in literature, RNFL thickness in patients with IIH was significantly higher in each quadrants tham among controls. 16,17 Studies on RNFL thickness in patients with ODD, however, have shown varying results. [18][19][20][21] Allegrini et al emphasized that ODD patients had a thinning of the RNFL and thought that this was due to the compression of the drusen material causing axonal damage.…”
Section: Discussionmentioning
confidence: 99%
“…Direct monitoring of intracranial pressure (ICP) is invasive and carries risks. Optical coherence tomography (OCT) is non-invasive and has demonstrated good potential as a surrogate measure of ICP in craniosynostosis [3,4]. Our group found good feasibility of handheld OCT in 50 children with craniosynostosis, demonstrating 86% success rate in at least one eye and 76% in both eyes [5].…”
mentioning
confidence: 83%
“…We have also demonstrated visualization of papilledema and RNFL loss in a preterm born child with obstructive hydrocephalus ( 33 ). More recently, investigators have suggested that OCT measures of the RNFL and retina may be a potentially sensitive indicator of elevated intracranial pressure in infants and young children such as with craniosynostosis ( 92 , 93 ); this remains to be validated, and we are not aware of reports for the preterm population. Others have shown that OCT imaging of RNFL thickness in infants and young children enables earlier identification of damage from optic nerve glioma, with ongoing validation studies ( 94 96 ).…”
Section: Optic Nerve and Retinal Nerve Fiber Layermentioning
confidence: 99%